2014
DOI: 10.3390/molecules190811915
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Micelles Composed of Doxorubicin Conjugated Y-Shaped PEG-Poly(glutamic acid)2 Copolymers via Hydrazone Linkers

Abstract: Abstract:In this work, micelles composed of doxorubicin-conjugated Y-shaped copolymers (YMs) linked via an acid-labile linker were constructed. Y-shaped copolymers of mPEG-b-poly(glutamate-hydrazone-doxorubicin) 2 and linear copolymers of mPEG-b-poly(glutamate-hydrazone-doxorubicin) were synthesized and characterized. Particle size, size distribution, morphology, drug loading content (DLC) and drug release of the micelles were determined. Alterations in size and DLC of the micelles could be achieved by varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Over the past few decades, there has been increasing interest in the potential use of NPs as delivery vehicles for chemotherapeutic drugs, and the studies have demonstrated that these nanocarriers can significantly enhance the anti-tumor efficiency of various chemotherapeutic drugs and also reduce or overcome the drug resistance of tumor cells [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, there has been increasing interest in the potential use of NPs as delivery vehicles for chemotherapeutic drugs, and the studies have demonstrated that these nanocarriers can significantly enhance the anti-tumor efficiency of various chemotherapeutic drugs and also reduce or overcome the drug resistance of tumor cells [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…S4 (ESI †), free Dox rapidly passed through the cell membrane and entered into the cell nuclei even in 2.5 h and at low dose which increases dramatically with incubation time and dose. 46,47 Owing to its hydrophobic anthracycline backbone and also very small size, Dox can pass through the cell and also nuclear membrane by diffusion which is driven by a concentration gradient across the membranes. 48,49 SPION-PNIPAM-Dox nanoparticles, on the other hand, are very efficiently internalized by endocytosis but cannot enter the nucleus.…”
Section: Endocytic Internalization Of Spion-pnipam-doxmentioning
confidence: 99%
“…87 Here, DOX was conjugated to a branched PEG- b -P(Glu) 2 copolymer via hydrazone linkages (Figure 7b). Noted differences between the branched PDCs and their linear counterparts include smaller micellar diameters (166 vs 231 nm) and a more rapid drug release rate for the branched architecture.…”
Section: Macromolecular Sapdsmentioning
confidence: 99%
“…Panel (a) was adapted from reference [86] with permission from the American Chemical Society (ACS), copyright 2013. Panel (b) was adapted from reference [87] with permission from the Multidisciplinary Digital Publishing Institute (MDPI), copyright 2014. Panel (c) was adapted from reference [88] with permission from ACS, copyright, 2016.…”
Section: Figmentioning
confidence: 99%